IMPLEMENTATION OF EDUCATIONAL GAMES BASED ON ROLE PLAYING GAMES (RPG) AS A LEARNING MEDIA FOR CHARACTER EDUCATION - Akhnaf, Ardhito Faza; Ayu, Winda Kusuma; A, Erico Pratama Nugraha (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2024)
The escalating issue of demoralization within the younger generation in Indonesia is exacerbated by the diminishing character values, often attributed to the pervasive influence of globalization. Recognizing the inadequacy of character education in schools, there is a pressing need for more engaging and interactive approaches to instill character in the youth. One promising avenue is leveraging games, given the prevalent engagement of young people in this activity. Among the various game genres, role-playing games (RPGs) stand out as particularly popular. This study, utilizing a literature review research method with descriptive analysis, aims to elucidate the implementation of RPG-based educational games as a medium for character education in the younger generation. The literature study findings underscore the potential of RPGs to serve as effective character education tools for adolescents, stimulating essential aspects such as ethical thinking, moral reasoning, value systems, friendship, self-scaffolding, and metacognition.